Application of titanium and titanium alloys to fixed dental prostheses. Issue 3 (July 2019) - Koizumi, Hiroyasu; Takeuchi, Yoshimasa; Imai, Hideyuki; Kawai, Tatsushi; Yoneyama, Takayuki
Abstract: Purpose: Titanium and titanium alloys are one of the main metallic materials in the medical and dental fields because of their biocompatibility. In this review, the application of titanium and its alloys as the substitute materials for Ag–Pd–Au alloy in the casting of fixed dental prostheses was examined. Study selection: A reference search was performed through PubMed based on the keywords titanium, titanium alloy, and dental casting. Other relevant references were obtained from the citation in the articles. Results: The dental casting technology for titanium has already been developed for clinical use, which enables the use of appropriate casting machines and investment materials for titanium and its alloys available commercially. The mechanical properties, castability, and corrosion resistance of titanium and titanium alloys were reported to be comparable or superior to the conventional dental alloys. Clinical researches reported that titanium and Ti-6Al-7Nb alloy casings showed suitable quality for clinical application. Conclusion: Titanium and its alloys can be the substitute materials for Ag–Pd–Au alloy, and should be considered worthy of qualifying for the dental insurance coverage.